Combining Diagnostics and Research in an Academic Laboratory - Waitz, Grit; Handtke, Stefan; Zaninetti, Carlo; Schönborn, Linda; Thiele, Thomas (Hämostaseologie, 2025)
Combining diagnostics and research in academic laboratories faces challenges and bears great opportunities. In this short review, we describe the objectives of diagnostic and research laboratories dealing with thrombosis and hemostasis questions. We give an overview of specific goals for diagnostic and research laboratories and explain the synergies and tasks which need to be managed in an interdisciplinary team.
Keywords: laboratory; research; diagnostics; thrombosis and hemostasis